Aktualisasi Fungsi Actuating dalam Penguatan Manajemen di Madrasah Ibtidaiyyah Swasta Hadirul Ulum - Rizky Mulia; Nailish Shofa Hidayah; Zaenal Mustakim; Rahmat Kamal (MGMP PAI SMP BINTAN, 2025)
This study aims to analyze the actualization of the actuating function in strengthening management at Madrasah Ibtidaiyyah, specifically MIS Hadirul Ulum. The problem studied is the optimal implementation of the actuating function in managerial practices at the madrasah level. The research uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation of the madrasah principal, teachers, and educational staff. The results of the study show that the actualization of the actuating function at MIS Hadirul Ulum is realized through the visionary leadership of the madrasah principal, continuous teacher empowerment, effective communication, the cultivation of Islamic values, and constructive academic supervision. The implementation of mobilization based on the principles of the Qur'an and Sunnah was able to improve teacher competence, strengthen Islamic work culture, and integrate the national curriculum with Islamic boarding school content to strengthen madrasah management.